A Comparison of App-Based Video-Modeling Interventions to Teach Physical Activity Skills to People With Autism in a Community Setting. Issue 4 (December 2021) - Bassette, Laura; Weissmann, Andrew; Pecsi, Emily; Seaman, Jenna
App-based technologies that utilize video-modeling components are an area that can increase the independence of people with autism spectrum disorder (ASD) in community settings; however, less is known about their impact in facilitating acquisition of physical activity (PA) skills in inclusive community fitness sites. It is important to consider how to increase PA skills in community settings for people with ASD given the known benefits of community inclusion and exercise. This study used an adaptive alternating treatment design to explore differences in three participants' ability to perform exercises independently in a community site when using commercial video-models (i.e., video-models available in the app) compared to custom-made video-models (i.e., developed by the researchers). Two participants performed the PA skills more independently when watching the custom-made videos while the third performed the PA skill more independently when watching the commercial video-models. All participants indicated they enjoyed using the app and videos to learn new PA skills. Limitations of the study as well as implications for future research are discussed.